The conceptual metaphor in Cusco quechua poetry: a cognitive semantic analysis of Nunaypa Rurun - Conchacalle Cáceres, Diana Ibelice (2019)
This paper introduces an analysis of metaphor as a cognitive semantic procedure in the work Nunaypa rurun: frutos del alma (1993) by the Cusco poet and anthropologist Delia Blanco Villafuerte. This analysis is framed within Cognitive Linguistics, which explains the construction of concepts through the existing relationship between language, thought and human experience, whose achievement is the structuring of abstract concepts in domains more concrete and closer to experience.